Fermented foods: a perspective on their role in delivering biotics - Vinderola, Gabriel; Cotter, Paul D.; Freitas, Miguel; Gueimonde, Miguel; Holscher, Hannah D.; Ruas-Madiedo, Patricia; Salminen, Seppo; Swanson, Kelly S.; Sanders, Mary Ellen; Cifelli, Christopher J. (Frontiers in Microbiology, 2023)
Fermented foods are often erroneously equated with probiotics. Although they might act as delivery vehicles for probiotics, or other ‘biotic’ substances, including prebiotics, synbiotics and postbiotics, stringent criteria must be met for a fermented food to be considered a ‘biotic. Those criteria include documented health benefit, sufficient product characterization (for probiotics to the strain level) and testing. Similar to other functional ingredients, the health benefits must go beyond that of the product’s nutritional components and food matrix. Therefore, the ‘fermented food’ and ‘probiotic’ terms may not be used interchangeably. This concept would apply to the other biotics as well. In this context, the capacity of fermented foods to deliver one, several, or all biotics defined so far will depend on the microbiological and chemical level of characterization, the reproducibility of the technological process used to produce the fermented foods, the evidence for health benefits conferred by the biotics, as well as the type and amount of testing carried out to show the probiotic, prebiotic, synbiotic and postbiotic capacity of that fermented food.